(untitled) (Journal of Forest and Livelihood, 2024)
Journal of Forestry and Livelihood ForestAction16 LIVELIHOODS, ECONOMIC OPPORTUNITY AND EQUITY The author highlights the successes of community forestry in improving local livelihoods. Using a livelihood framework, he assesses the nature and extent of contributions of community forestry in improving the different livelihoods capitals – including social and human, natural, and physical. He also identifies broader positive changes in social, organizational and policy aspects. Finally, some challenges ahead are also identified.